Synthesis and characteristics of bamboo-based activated carbon as electrode materials - Azmi, Nurul Izzah; Poh, Xua Lian; Wan Abdul Karim Ghani, Wan Azlina; Sobri, Shafreeza; Haris, Nur Izzah Nabilah; Kamsani, Noor’Ain; Alias, Azil Bahari (2025)
The growing demand for sustainable energy storage solutions has intensified research into biomass-derived materials as eco-friendly alternatives to conventional components. Bamboo, a rapidly renewable and abundant resource, exhibits unique structural properties, making it a promising candidate for high-performance activated carbon. This study bamboo-based activated carbon was activated at 120°C to 160°C with potassium hydroxide for one hour, followed by extensive washing with deionized water and drying in a vacuum desiccator for 3 days. Characterization using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and cyclic voltammetry (CV)measurements revealed its porous structure and functional diversity. Optimal performance was achieved at 7% KOH concentration and a scan rate of 75 mV/s, demonstrating a high specific capacitance and excellent cyclic stability with retention rate exceeding 90%. These results highlight bamboo’s viability as a sustainable, high-performance electrode material, offering promising solutions for advancing green energy storage technologies.